Assessed impact of anthropization on water and soil quality in a drainage basin in southern Brazil - Wroblescki, Filipe Antonio; Bertol, Ildegardis; Wolschick, Neuro Hilton; Bagio, Bárbara; Santos, Venesa Pinto dos; Bernardi, Loriane; Biasiolo, Luiz Antonio (Revista de Ciências Agroveterinárias, 2021)
The anthropization of terrestrial environments has increased the production and concentration of nutrients and organic compounds in shallow bodies of water and in the soil along river banks, thereby causing changes in both water and soil quality. To examine the impact of anthropization on river environments, the phosphorus, potassium, and carbon content in the water and the phosphorus, potassium, and organic matter in the soil were analyzed at eighteen sites. The experimental area is located in an urbanized drainage basin located in the municipality of Lages, Santa Catarina (southern Brazil). The water samples were collected in two field surveys. The first one occurred between August and December 2016, and the second took place from March to June 2017. The soil samples were collected in one field survey from August 2016 and June 2017. The 18 sites were regularly distributed across forests, native grasslands, and urban areas. The dissolved phosphorus and potassium in the water were obtained by applying the methodology proposed by MURPHY & RILEY (1962), whereas the dissolved carbon in the water was mineralized by combustion using an oven at 800 ºC and calculated with the Analytik Jena Multi N/C 2100 TOC/TN Analyzer. On the other hand, the extractable phosphorus and potassium from the soil and organic matter were determined with the methodology described by TEDESCO et al. (1995). The results demonstrated that the concentration of dissolved phosphorus, potassium, and carbon in the water was greater in the parts of the river that cross through urban areas than in the parts of the river that course through grasslands and forests throughout practically the entire year. The same trend was observed with the phosphorus and potassium content in the soil along the river banks. However, the organic matter content in the soil was lower in the sections located in urban areas. The findings indicate that in urban areas where sewage treatment is either nonexistent or deficient, the release of domestic wastewater containing household detergents and soaps contributes to the increase in the content of phosphorus, potassium, and carbon in the water and phosphorus and potassium in the soil.